Measurement errors affecting the characteristics of multi-position systems, and ways to reduce them - Аrtikula, A.; Britov, D.; Dzhus, V.; Haibadulov, B.; Haibadulova, A.; Herasymov, S.; Kaluhin, D.; Kukobko, S.; Roshchupkin, Y.; Tytarenko, R. (interconf, 2021)
Modern wide development of science and technology causes the growth of information needs in all branches of human development. At present, there are all opportunities to increase information security by combining sources of information into a single system. At the same time, when merging, specific difficulties and features emerge, which together make it difficult to implement the proposed solutions. The paper considers the peculiarity of combining different types of radar stations into a single information system. Errors of measurements of separate parameters and their influence on system characteristics are considered. Options for solving the problems that have arisen are proposed.
Keywords: information integration; measurement error; multi-position system; unified coordinate system